(3GdbGfhf GdEOGQj (B:s (3eGgjI GdbGfhf GdEOGQj(B-(3GdJfXje GdEOGQj(B-(3GdfTGW GdEOGQj (B= Administrative law : definition of administrative law-administrative organizing-administrative activity /s - (3GdWgQGhj, gGfj Ydjs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2014)
(3JHQR CgejI gPG GdcJGH(B((3GdbGfhf GdEOGQj(B) (3dOQGSI bGfhf jMce Jchjf hJfXje GdSdWI GdEOGQjI hjMOO GNJUGUgG hYdGbGJgG HdCaQGO heOi JONdgG aj JfXje CfTWJge hJhLjggG Vef GdCWQGa GdJj jQSegG GdbGfhf hef GdedGMX CROjGO CgejI gPG GdbGfhf hNGUI HYO GJSGY hJYOO GdeLGdGJ hGdejGOjf GdJj EeJOJ EdjgG CPQY GdEOGQI hCfTWJgG gGOaI Edi JbOje GdeRjO ef GdNOeGJ dehGWfjgG(B.s
(3JUeje (B: (3GdKbGaI ddJUeje hGdENQGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B325-335.s
Keywords: (3GdbGfhf GdEOGQjs -- (3GdCQOfs; (3GdEOGQI GdYGeIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs